Transforming military power since the Cold War Britain, France, and the United States, 1991-2012 - Farrell, Theo; Rynning, Sten; Terriff, Terry (Cambridge University Press, 2013)
A deeply researched account of how the British, French and US armies have transformed themselves since the end of the Cold War. This is an essential reference for anybody studying contemporary military development, the US military, European defence, and the future of military power.